Physical properties and water absorption kinetics of three varieties of Mucuna beans - Ajibola B. Oyedeji (Nature Portfolio, 2021)
Abstract The physical properties and water absorption kinetics of three varieties of Mucuna beans (Mucuna pruriens, Mucuna rajada and Mucuna veracruz) were determined in this study. Physical properties including length, width, thickness, geometric mean diameter, sphericity, porosity, bulk density, area, volume and one thousand seed mass were calculated while hydration kinetics was studied by soaking Mucuna beans in water at 30 °C, 40 °C and 50 °C and measuring water uptake at 9 h interval. Peleg’s equation was used to model the hydration characteristics and Arrhenius equation was used to describe the effect of temperature on Peleg’s rate constant k1 and to obtain the activation energies for soaking. Significant variations were observed in almost all the physical properties of the different varieties, however, there were no significant differences (p < 0.05) in their thicknesses and bulk densities. The effectiveness of fit of Peleg’s model (R2) increased with increase in soaking temperature. Peleg’s rate constant k1 decreased with increase in soaking temperature while k2 increased with temperature increase. Activation energies of Mucuna pruriens, Mucuna rajada and Mucuna veracruz were 1613.24 kJ/mol, 747.95 kJ/mol and 2743.64 kJ/mol, respectively. This study provides useful information about the properties of three varieties of Mucuna beans that could be of importance to processors and engineers for process design and optimization.